2022
DOI: 10.13057/biodiv/d230714
|View full text |Cite
|
Sign up to set email alerts
|

Identification of spatial data and ecology of Javan hawk-eagle's nest (Nisaetus bartelsi) in the Kondang Merak Coastal, South Malang, East Java, Indonesia

Abstract: Abstract. Iskandar RRD, Elfidasari D, Prawiradilaga DM. 2022. Identification of spatial data and ecology of Javan hawk-eagle's nest (Nisaetus bartelsi) in the Kondang Merak Coastal, South Malang, East Java, Indonesia. Biodiversitas 23: 3419-3428. Ecological identification of the Javan hawk-eagle's habitat (Nisaetus bartelsi) is necessary to understand the support of its life, such as the spatial data in connection with its home range, nest location, and the use of nest trees. The species must choose a location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…According to van Balen et al (1999), this bird has been present in the southern region of East Java since 1997. Ardiansyah et al (2015) also found this bird in three locations, while Iskandar et al (2022) reported breeding success in the Kondang Merak Beach Protection Forest. Therefore, the presence of Javan hawkeagle in Kondang Merak Protection Forest should be continuously monitored to support its sustainability.…”
Section: Introductionmentioning
confidence: 85%
“…According to van Balen et al (1999), this bird has been present in the southern region of East Java since 1997. Ardiansyah et al (2015) also found this bird in three locations, while Iskandar et al (2022) reported breeding success in the Kondang Merak Beach Protection Forest. Therefore, the presence of Javan hawkeagle in Kondang Merak Protection Forest should be continuously monitored to support its sustainability.…”
Section: Introductionmentioning
confidence: 85%